Acetylcholinesterase-responsive fluorescent probe: Recent advances from development to applications - An, Jong Min; Jung, Kyung Oh; Oh, Myung Sook; Kim, Dokyoung (Elsevier BV, 2023)
The correlation between diseases and acetylcholinesterase (AChE) has been highlighted in the medical field. In this regard, the AChE-responsive fluorescent probes can enhance the prevention of unexpected human diseases. Herein, we discuss the recent advances in AChE-responsive fluorescent probes capable of detecting the AChE expression and monitoring the AChE activity in real time. The fluorescent probes for AChE can be categorized into three parts based on the AChE sensing rationale. Photophysical properties of the AChE-responsive fluo-rescent probes and representative examples of the proof-of-concept AChE-related visualization studies are also summarized. We hope that this review will inspire the development of AChE-responsive fluorescent probes and contribute to improving overall health conditions worldwide.